Human thrombomodulin regulates complement activation as well as the coagulation cascade in xeno‐immune response. (14th July 2015) - Kim, Hwajung; Hawthorne, Wayne J.; Kang, Hee Jung; Lee, Yoo Jin; Hwang, Jong‐Ik; Hurh, Sunghoon; Ro, Han; Jeong, Jong Cheol; Cho, Bumrae; Yang, Jaeseok; Ahn, Curie
Abstract Background With the introduction of the α1, 3‐galactosyltransferase gene‐knockout (GT‐KO) pig and its pivotal role in preventing hyperacute rejection (HAR), coagulation remains a considerable obstacle yet to be overcome in order to provide long‐term xenograft survival. Thrombomodulin (TBM) plays a critical anticoagulant and anti‐inflammatory role in its part of the protein C pathway. Many studies have demonstrated the strong anticoagulant effects of TBM in xenotransplantation, but its complement regulatory effects have not been appropriately examined. Here, we investigate whether TBM can regulate complement activation as well as coagulation in response to xenogeneic stimuli. Methods We transfected porcine endothelial cells (MPN‐3) with adenovirus vectors containing the human TBM gene (ad‐hTBM), or a control gene containing GFP (ad‐GFP). The expression level of ad‐hTBM was measured by flow cytometry. To confirm the anticoagulant effect of TBM, coagulation time was measured after treatment with recalcified human plasma in ad‐hTBM‐transfected MPN‐3, and a thrombin activity assay was performed after treatment with 50% human serum in ad‐hTBM‐infected MPN‐3. Results Thrombin generation was significantly decreased in a dose‐dependent manner in ad‐TBM group, and coagulation time was increased in the ad‐hTBM group when compared to the ad‐GFP group. Complement‐dependent serum toxicity assays were performed after treatment with 20% human serum or heat‐inactivated human serum by LDH assay. Complement‐dependent toxicity was significantly attenuated in the ad‐hTBM group, but complement‐independent toxicity was not attenuated in the ad‐hTBM group. These results suggest that human thrombomodulin (hTBM) has complement regulatory effects as well as anticoagulant effects. To further investigate the mechanisms of complement regulation by hTBM, we deleted the EGF5, 6 domains that are involved in thrombin generation or the lectin‐like domain involved in inflammation of TBM and functional tests were performed using these modified forms. We showed that the EGF5, 6 domain of TBM principally inhibits complement activation rather than the lectin domain. Conclusion The EGF5, 6 domains of TBM appear to be the major domains for down‐regulating the complement system rather than the lectin‐like domain during xenogenic stimuli. The role of EGF5, 6 domains of hTBM may be due to inhibition of thrombin as thrombin can cleave C3a and C5a directly and hTBM may also be involved in complement regulation. Clearly then human TBM has complement regulatory effects as well as anticoagulant effects in xeno‐immune response, and it is a promising target for attenuating xenograft rejection.